Habitat and Distribution Modeling of Prehistoric Hippos (Hippopotamus sivalensis spp.) During Pleistocene in Java Island - Andriwibowo, Andriwibowo; Basukriadi, Adi; Nurdin, Erwin (Jurnal Biodjati, 2021)
Currently, there are only 2 extant species of hippos including common (Hippopotamus amphibius) and pygmy hippos (Choeropsis liberiensis) . But in prehistoric times, there were several species. During Pleistocene these species were known to migrate to Java Island from Asian Continent and the species was Hippopotamus sivalensis spp. In this regard, this study aimed to model the habitat of H. sivalensis spp., ecology, and biodiversity of Hippopotamus sivalensis spp. based on the fossil record. The model was developed based on the Principal Component Analysis (PCA) method using the R statistical package. The results showed that there were 7 populations of H. sivalensis spp. that lived at various altitudes with an average of 177 m above sea level (95% CI : 123-232 m). According to PCA, there were at least 2 separate populations of H. sivalensis spp. One population occupies the forest while another occupies a habitat close to the coast. Currently the habitat for H. sivalensis spp. already changed. Based on habitat modeling, H. sivalensis spp. inhabit streams with submerged aquatic plants and shrubs and trees growing along river banks.